Pemanfaatan Teknologi Informasi dan Transformasi Sakralitas Al-Qur’an di Abad Ke-20 dan 21 - Najmuddin, Ahmad; Nurulita, Dwita (Indonesian Proceedings and Annual Conference of Islamic Law And Sharia Economic (IPACILSE), 2023)
This research investigates the information technology utilization on the Qur’an in the era of digital revolution. Through a qualitative approach and literature study, this research explores the changing values related to the sacredness of the Qur’an. The analysis involved the concepts of Qur’anic sacredness, information technology, digital revolution and information technology utilization. The result show significant transfirmations in the way the Qur’an is studies, accessed dan viewed in the digital era. The transformations that occur have implications and challenges for Muslims to maintain their religious values, especially related to the sacredness of the Qur’an.